Historis Umat Islam dalam Menjaga Otentisitas Al-Qur’an - Achmad Syauqi Hifni (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The Qur'an is a very central text in religious studies. In particular, the study of the authenticity of the Qur'an has invited several researchers and academics to criticize it. Even among Muslims themselves there is also controversy between several sects. As in the case of the Siah sect, they considered that Uthman>n's codification of the Qur'an was inaccurate and not objective. So that this raises doubts for some people in the Siah sect about the authenticity of the Qur'an. Likewise, orientalists also doubt the authenticity of the Qur'an. To see the authenticity of the Koran, this paper tries to describe how the history, methods and efforts of Muslims in protecting the Koran? This paper is prepared based on qualitative methods, presented based on descriptive analysis. Data was collected from literature review (library research). Through the results of the study it was found that: from a historical perspective, the preservation of the Qur'an has been preserved since the time of the Prophet, companions, tabiin, to the contemporary era. From the method aspect, Muslims protect the Koran with two methods, namely memorization (hifzi) and written media (kita>bah).